(untitled) (Global Journal of Human-Social Science, 2014)
People use stories to construct meaning and to communicate. The skills of storytelling are crucial for engaging in casual conversation and successful communication in general. In the 21st century children are faced with various modalities of representation, which require new ways of reading, listening, interpreting and thinking. Children are engaged in those different modes of interaction and the nonlinear and multimedia world. Along with the advance of technology, the classic storytelling has also seen some developments in EFL classrooms around the world. In a modern classroom it is necessary to address multiple literacies and digital storytelling combines the ancient art of telling stories with a variety of digital tools and multimedia. Computer-aided storytelling has become an important tool of instruction for students of English as a foreign language, as well as their educators. This article aims to present an overview of the practical uses of computer-aided storytelling in English language classrooms. Nevertheless, the implementation of the aforementioned instructional tools in EFL classrooms entails different challenges for both students and educators. The paper includes the discussion of the most important benefits and challenges of computer-aided storytelling.